Pakistan Development Update, May 2017 : Growth - A Shared Responsibility - World Bank (World Bank, Islamabad, 2017)
Pakistan's economy continues to grow strongly, emerging as one of the top performers in South Asia. Beneath the surface, however, a number of warning signs are emerging. Revenue growth is slowing, with the fiscal deficit growing for the first time in three years. Exports continue to fall as imports grow, substantially increasing the current account deficit. Investment rates - already low - fell further in FY16 (the latest data available). Finally, the energy sector circular debt has resurfaced. These emerging concerns suggest that renewed policy emphasis is required on macroeconomic stability - to prevent the country from losing the impressive gains achieved over the past four years - and other structural reforms such as those required in the energy sector. While the federal government necessarily carries the majority of this burden, provincial governments also have a part to play. The special sections of this update analyze some of the specific challenges facing Pakistan's most populous province, Punjab, including increasing own-source revenue, equipping youth with employable skills and ensuring the poor share in the benefits of growth. Punjab, along with federal and other provincial governments, is also confronted with the urgent task of lifting agricultural productivity and addressing distortive subsidies, which are impeding growth.